Local Self-Governments in Hungary: Recent Changes through Central European Lenses - Csaba Lentner; Szilard Hegedus (Central European Public Administration Review)
This article provides an overview of the regulatory environment of the Hungarian system of local self-government based on the methods of legal dynamics and economic analyses in a historical perspective tracing events back to the aftermath of World War II. The starting point of the analysis is 1947, the launching of soviet type command economy in Hungary. Next is a detailed study of the regulation and evolution of local self-government since its beginnings in the early 1990s following the change of regime, with a brief international outlook on the post-soviet countries surrounding Hungary. In our economic analysis, emphasis is placed on the period following Hungary’s accession to the European Union, a period that held out considerable opportunities for Hungarian local self-governments, but ultimately evolved into bankruptcy. The article presents detailed reasons for the atypical nature of Hungarian local self-government indebtedness and the factors underlying this unfavourable process. Further on, the procedure of debt consolidation and the essential elements of the new regulatory environment created after 2011 are described. In a brief international comparison, debt portfolio developments are analysed through the examples of Slovenia, Poland, Slovakia and the Czech Republic as analogue Central European countries, in order to provide further proof of the atypical financial management of Hungarian local self-governments, i.e. non-compliance with the rules and the not always solid budgetary discipline. The focus of the research underlying this paper is the impact the Hungarian regulation of self-governments had on the financial sustainability of local self-governments’ financial management. The study confirmed the initial hypothesis that the business management rules set out with insufficient prudence, deficiencies in the control system, and excessive borrowing in foreign exchange led to bankruptcy of a number of local self-governments and consequently jeopardised the proper provision of public services.